Pola Asuh Demokratis dan Pelopor: Strategi Menghadapi Tantangan Pendidikan Anak di Era Globalisasi - Sumitro, Wiwid Hadi; Windayani, Windayani (Instructional Development Journal, 2025)
Children are a trust given to us by God. In maintaining this trust, the right method is used, namely by building, nurturing and caring for it carefully so that one day it will become a complete human being. The smallest unit in society is the family, where the family is built through a marriage bond consisting of father, mother and children. The family is the main source in providing a role in the physical and psychological development of children. Based on the background of this problem, what are the parenting patterns of parents towards children in the era of globalization? The aim of this research is to determine parents' parenting patterns for children in the era of globalization. This research method is this research uses a literature review design which aims to obtain information about parenting patterns regarding children's education in the era of globalization. The results of this research are that parenting patterns in children's education in the era of globalization are very important. According to the author, effective parenting models are democratic parenting and pioneer parenting. Parenting patterns in children's education in the era of globalization include parenting patterns in terms of; faith education, moral education, physical education, intellectual education, psychological education, social education, and sex education.